The Effect of After Sales Service on Online Shop Consumer Satisfaction (Survey of Tokopedia and Shopee Consumers at Kadiri University) - Nonni Yap; Afif Nur Rahmadi; M Dian Ruhamak; Risma Gesang Ayu; Anindhitya Sofi M; Oktaviani Wahyu Prihardini (JPIM (Jurnal Penelitian Ilmu Manajemen), 2022)
Keywords : Online shop, strategy, platform, turnover, market